2010
DOI: 10.1121/1.3466879
|View full text |Cite
|
Sign up to set email alerts
|

Production of French vowels by American-English learners of French: Language experience, consonantal context, and the perception-production relationship

Abstract: Second-language (L2) speech perception studies have demonstrated effects of language background and consonantal context on categorization and discrimination of vowels. The present study examined the effects of language experience and consonantal context on the production of Parisian French (PF) vowels by American English (AE) learners of French. Native AE speakers repeated PF vowels /i-y-u-oe-a/ in bilabial /bVp/ and alveolar /dVt/ contexts embedded in the phrase /raCVCa/. Three AE groups participated: speaker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
67
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 36 publications
6
67
1
Order By: Relevance
“…In other words, they may have simply been drawing upon vowel tokens that were already in their repertoire: particularly fronted versions of English /u/. It has been proposed that due to the fact that American English /u/, which is already relatively front on average, is further fronted in the context of alveolars, the front vowel /y/ may not actually constitute a "new" vowel for English-speaking L2 learners, but instead a "similar" vowel, at least in the context of alveolars (Strange et al, 2007;Levy, 2009;Levy and Law, 2010). Documented perceptual assimilation patterns in which English speakers identify German and French /y/ as closest to English /u/ (e.g.…”
Section: B "New" Vs "Similar" Categoriesmentioning
confidence: 99%
“…In other words, they may have simply been drawing upon vowel tokens that were already in their repertoire: particularly fronted versions of English /u/. It has been proposed that due to the fact that American English /u/, which is already relatively front on average, is further fronted in the context of alveolars, the front vowel /y/ may not actually constitute a "new" vowel for English-speaking L2 learners, but instead a "similar" vowel, at least in the context of alveolars (Strange et al, 2007;Levy, 2009;Levy and Law, 2010). Documented perceptual assimilation patterns in which English speakers identify German and French /y/ as closest to English /u/ (e.g.…”
Section: B "New" Vs "Similar" Categoriesmentioning
confidence: 99%
“…However, the relation between the two abilities is rather complex and still a matter of debate. This seems due to the fact that there is not a well-established link in terms of empirical evidence (Levy & Law, 2010). In fact, some studies have found an opposite pattern where production precedes perception.…”
Section: Introductionmentioning
confidence: 79%
“…There are a number of studies that support these theoretical claims and have identified a link between perception and production (e.g., Flege, Bohn, & Jang, 1997;Levy & Law, 2010;Morrison, 2003Morrison, , 2006Rallo Fabra & Romero, 2012;Rauber, Escudero, Bion, & Baptista, 2005). In particular, these studies suggest that a learner's perception of the L2 influences their production of the L2 (Levy & Law, 2010;Llisterri, 1995;Morrison, 2003).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the investigation, we focus on the acquisition of the French phoneme /y/ (as in tu /ty/ 'you') for two main reasons: (1) the sound is highly difficult to acquire in both production and perception (e.g. Baker and Smith, 2010;Levy and Law II, 2010;Rochet, 1995); and (2) it has a high functional load in the target language (Jenkins, 2002;King, 1967), as it is used to distinguish many French minimal pairs such as au-dessous /od.su/ 'below' and au-dessus /od.sy/ 'above'. To our knowledge, there are no studies that have investigated the use of ASR on mobile devices for pronunciation teaching (see also Godwin-Jones, 2009, for a similar observation).…”
Section: Introductionmentioning
confidence: 99%